Efficacy of 12-weeks velpatasvir plus sofosbuvir-based regimen in HCV-naive subjects with mild fibrosis: a meta-analysis - Pisaturo, Mariantonietta; Russo, Antonio; Onorato, Lorenzo; Coppola, Nicola (Acta Biomedica Atenei Parmensis, 2019)
Background and aims: In literature systematic data on treatment with the fixed-dose combination of sofosbuvir and velpatasvir for 12 weeks in anti-HCV/HCV RNA positive subjects with mild fibrosis and naïve to previous Interferon free regimen are scanty. A meta-analysis has been performed to evaluate the efficacy of velpatasvir plus sofosbuvir combination in these patients. Methods: All randomized or non-randomized studies,  investigating the sustained virological response rate to sofosbuvir plus velpatasvir without ribavirin for 12 weeks in subjects naïve to previous DAA therapy and with fibrosis F0-F2 or F0-F3, were included in the meta-analysis. Results: A total of 16 studies enrolling 4,907 subjects met the inclusion criteria and were included in this meta-analysis. The prevalence of SVR by sofosbuvir and velpatasvir was 98% (95% CI 96-99%) in the 4,907 subjects without cirrhosis. The prevalence of SVR was similar considering the 9 clinical studies and the 7 real-world studies (98%, CI 95%: 96-99% and 98%; CI 95%: 96-99%, respectively). Considering the 4 studies enrolling 1,371 subjects without advanced liver fibrosis the prevalence of SVR was also high [96% (95% CI: 94-98%)]. Data indicate a prevalence of SVR ranging to 95-100% according to the different HCV genotypes. Conclusion: Sofosbuvir plus velpatasvir therapeutic regimen was highly effective in HCV patients without advanced liver disease naïve to previous DAA regimen independently the different HCV genotypes.